(untitled) (Revista Apotheke, 2021)
This article presents the relationship between art and technology in the formation of a new image paradigm. Its object is the critical reflection of the transformations that occurred in the production of images, specifically in the hybrid images of the current illustrations arising from the dialogue between the areas of art and graphic design. This is a qualitative research of a bibliographic nature with the proposition of empirical work, with the ultimate goal of producing an illustration work in the expanded field